Addizione: Nuovo complesso Santa Teresa 2006-2016 - Breschi, Alberto (AND Rivista di architetture, città e architetti)
The new project aimed at the full recovery of the entire St. Teresa prison complex was an opportunity to re-functionalize disused spaces and implement a real metamorphosis that has changed, first and foremost, the atmosphere.